Performance evaluation of FTiO2-POE nanolubricant for enhanced efficiency in automotive air conditioning systems - Prayogo, Galang Sandy; Rizalman, Mamat; Mohd Fairusham, Ghazali; Azmir, Azhari; Erdiwansyah, .; Nuraini, Lusi; Nugroho, Agus; Muriban, Jackly (Elsevier B.V., 2026)
Automotive air conditioning (AAC) systems significantly contribute to vehicle fuel consumption and greenhouse gas emissions, making efficiency improvement a critical priority. Conventional lubricants, such as polyol ester (POE) oils, suffer from low thermal conductivity, poor lubricity, and instability under high thermal stress, limiting system performance. This study introduces GPTMS-functionalized titanium dioxide (FTiO2) nanoparticles into POE lubricants to enhance dispersion stability and thermal–tribological properties. Experiments were conducted using a vehicle-scale AAC test rig with R1234yf refrigerant under varying compressor speeds (2000–5000 rpm) and refrigerant charges (210–360 g). Four nanolubricant concentrations (0.02–0.08% vol.) were evaluated in terms of cooling capacity, compressor work, power consumption, and coefficient of performance (COP). The results show that functionalization improves nanoparticle stability and system performance. The highest concentration (0.08%) provides maximum thermal performance, increasing heat absorption by 4–7%, reducing compressor work by up to 25%, and achieving peak COP values of 6.2, 3.8, and 2.83 at 2000, 3500, and 5000 rpm, respectively. However, this concentration also increases viscosity, leading to higher power consumption. In contrast, the 0.04% concentration yields the lowest power consumption and represents the most energy-efficient formulation at high speeds. These findings highlight a trade-off between enhanced heat transfer and viscosity-induced energy loss. Therefore, 0.08% is optimal for maximum cooling performance, while 0.04% is optimal for energy efficiency. Overall, FTiO2–POE nanolubricants offer a promising solution for improving AAC system performance under realistic operating conditions.